Cyclic AMP-dependent and Epac-mediated activation of R-Ras by G protein-coupled receptors leads to phospholipase D stimulation - De Jesús, Maider López; Stope, Matthias B; Weernink, Paschal A Oude; Mahlke, Yvonne; Börgermann, Christof; Ananaba, Viktoria N; Rimmbach, Christian; Rosskopf, Dieter; Michel, Martin C; Jakobs, Karl H; Schmidt, Martina (The Journal of biological chemistry, 2006)
The activation of the Ras-related GTPase R-Ras, which has been implicated in the regulation of various cellular functions, by G protein-coupled receptors (GPCRs) was studied in HEK-293 cells stably expressing the M3 muscarinic acetylcholine receptor (mAChR), which can couple to several types of heterotrimeric G proteins. Activation of the receptor induced a very rapid and transient activation of R-Ras. Studies with inhibitors and activators of various signaling pathways indicated that R-Ras activation by the M3 mAChR is dependent on cyclic AMP formation but is independent of protein kinase A. Similar to the rather promiscuous M3 mAChR, two typical G(s)-coupled receptors also induced R-Ras activation. The receptor actions were mimicked by an Epac-specific cyclic AMP analog and suppressed by depletion of endogenous Epac1 by small interfering RNAs, as well as expression of a cyclic AMP binding-deficient Epac1 mutant, but not by expression of dominant negative Rap GTPases. In vitro studies demonstrated that Epac1 directly interacts with R-Ras and catalyzes GDP/GTP exchange at this GTPase. Finally, it is shown that the cyclic AMP- and Epac-activated R-Ras plays a major role in the M3 mAChR-mediated stimulation of phospholipase D but not phospholipase C. Collectively, our data indicate that GPCRs rapidly activate R-Ras, that R-Ras activation by the GPCRs is apparently directly induced by cyclic AMP-regulated Epac proteins, and that activated R-Ras specifically controls GPCR-mediated phospholipase D stimulation.